DESIGNING A TRAPEZOIDAL MODULAR BLOCK WALL WITH NONLINEAR OPTIMIZATION - Vuttichai Chatpattananan (My University, 2022)
A rectangular wall is better in terms of stability and ease of calculation than a trapezoidal wall. However, a trapezoidal wall is sometimes inevitable such as a retaining wall construction near rockface. FHWA provides simplified rules to design a trapezoidal wall. However, FHWA does not give an example to follow, and the rules need trial and error to implement. BS8006 gives an exact dimension of the block heights, but designing still needs to adjust the block widths. A 16-meters high modular block wall project near rock face in Thailand as an example to illustrate a calculation detail in external stability checking follow FHWA simplified rules and BS8006. The illustrations are trapezoidal walls with two zones, three zones, and four zones. Nonlinear optimization models are also used to minimize the wall base length to facilitate the construction instead of jacking the near rock face to build a rectangular wall. Optimization models also help to relax FHWA simplified rules and BS8006 guidelines. Using an optimization model can decrease the base length from 0.7H to 0.6H for a rectangular wall or even 0.5H for a rectangular wall with competent foundation soil. Optimization models can also achieve a base length down to 0.48H with a decrease in the cross-sectional area down to 0.92 for a three zones trapezoidal wall. A simple three zones wall with exact dimensions is also proposed in the competent foundation soil conditions.
Keywords: Base (topology); Foundation (evidence); Geotechnical Engineering and Underground Structures